2010
DOI: 10.4240/wjgs.v2.i10.324
|View full text |Cite
|
Sign up to set email alerts
|

Imaging considerations in intraductal papillary mucinous neoplasms of the pancreas

Abstract: With the widespread use of cross-sectional imaging, particularly computed tomography (CT) and magnetic resonance imaging (MRI), and the continuous improvement in the image quality of these techniques, the diagnosis of incidental pancreatic cysts has increased dramatically in the last decades. While the vast majority of these cysts are not clinically relevant, a small percentage of them will evolve into an invasive malignant tumor making their management challenging. Mucinous cystic neoplasms and intraductal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Given that CT has advantages over MR imaging with MRCP in terms of spatial resolution and wider availability and that MRCP is more useful than CT in evaluating ductal communication and abnormalities, at many institutions, both modalities are equally used to evaluate patients with IPMNs and interchangeably used to follow-up patients with IPMNs (12,13,20,22,23). Although several previous studies demonstrated that both CT and MR imaging can be useful in determining the malignant potential of IPMNs, until now, there were no studies that assessed the intermodality agreement for depicting stigmata and worrisome features at CT or MR imaging (13,20,(24)(25)(26)(27)(28)(29). On the basis of our study results, which showed good intermodality agreement between multidetector CT and MR imaging, we believe that multidetector CT and MR imaging can be interchangeably used for the evaluation of malignant potential in IPMNs, as well as for follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Given that CT has advantages over MR imaging with MRCP in terms of spatial resolution and wider availability and that MRCP is more useful than CT in evaluating ductal communication and abnormalities, at many institutions, both modalities are equally used to evaluate patients with IPMNs and interchangeably used to follow-up patients with IPMNs (12,13,20,22,23). Although several previous studies demonstrated that both CT and MR imaging can be useful in determining the malignant potential of IPMNs, until now, there were no studies that assessed the intermodality agreement for depicting stigmata and worrisome features at CT or MR imaging (13,20,(24)(25)(26)(27)(28)(29). On the basis of our study results, which showed good intermodality agreement between multidetector CT and MR imaging, we believe that multidetector CT and MR imaging can be interchangeably used for the evaluation of malignant potential in IPMNs, as well as for follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The MR criteria used in our study for the diagnosis of malignant IPMNs or invasive IPMCs were established based on the reported findings or suggested criteria from the previous studies (1,8,10,(19)(20)(21)(22)(23), which were based mainly on the features of main cystic tumor lesions, and associated findings such as the changes in the main pancreatic duct and the bile duct and pancreatic parenchymal changes (Figs. 1, 2).…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Multirow detector computed tomography (MDCT) or magnetic resonance imaging (MRI) is often the first imaging ordered when the diagnosis of a pancreatic cystic neoplasm is considered (6,7). Several previous studies (1,4,(8)(9)(10)(11) on MRI and CT have demonstrated that a tumor size greater than 3-5 cm, MPD dilation greater than 5-10 mm, a thick septum, mural nodule or a parenchymal mass, and local invasion are associated with malignancy. Therefore, to stratify a malignancy and for therapeutic decision-making, it is necessary to precisely evaluate ductal changes as well as the presence of mural nodules or parenchymal involvement as seen on imaging studies.…”
mentioning
confidence: 99%
“…Even though CT is still a mainstay in the evaluation of the surgical resectability of pancreatic IPMNs with a strong preference among pancreatic surgeons, MR imaging with MRCP has come into wide acceptance in recent days (7,14,(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%